Effectiveness of an ergonomic intervention to reduce musculoskeletal discomfort - Cardoso, Bárbara (2021)
Musculoskeletal discomfort is common among office workers, being related to individual, workplace and behaviors risk factors. Ergonomic interventions are of particular importance to reduce musculoskeletal discomfort. However, only few have studied the impact of an ergonomic intervention on these symptoms reduction. This study aims to design and implement an intervention program to reduce musculoskeletal symptoms in office workers. A total of 84 employees from a charity and social assistance institution were involved in the study. The intervention included training actions to all employees, delivery of informative pamphlet and modifications in workplaces. To assess the intervention effectiveness, a questionnaire with a scale to assess musculoskeletal discomfort was applied in three moments: Pre-intervention; Post intervention Moment 1 and Post-intervention Moment 2. The areas described with greater musculoskeletal discomfort in the three moments were the neck, lower back, upper back and right shoulder. Between Pre-intervention and Post intervention Moment 1, there was a tendency to reduce musculoskeletal discomfort at the end of the day in all regions analyzed. It was also found a stagnation of discomfort in some regions of the body, comparing the Moment 1 and Moment 2 Post-intervention. Significant improvements in upper back and neck at the end of the workday were observed. This study suggests that an ergonomic intervention program has advantages for the employees' health, promoting the reduction of musculoskeletal symptoms